Alligatorweed thrips (suggested) Amynothrips andersoni O'Neill (Insecta: Thysanoptera: Phlaeothripidae) - Ted D. Center; James P. Cuda; Michael J. Grodowitz (EDIS, 2010)
EENY-476, a 3-page illustrated fact sheet by Ted D. Center, James P. Cuda, and Michael J. Grodowitz, is part of the Featured Creatures collection. It describes this natural enemy of alligatorweed – distribution, description, hosts, life cycle, and economic importance. Includes references. Published by the UF Department of Entomology and Nematology, June 2010.